A Novel Approach to First-Rib Resection in Neurogenic Thoracic Outlet Syndrome - Li, Yueying; Liu, Yanxi; Zhang, Zhan; Gao, Xuehai; Cui, Shusen (Frontiers in Surgery, 2021)
Objectives: The treatment for neurogenic thoracic outlet syndrome (NTOS) conventionally involves first-rib resection (FRR) surgery, which is quite challenging to perform, especially for novices, and is often associated with postoperative complications. Herein, we report a new segmental resection approach through piezo surgery that involves using a bone cutter, which can uniquely provide a soft tissue protective effect. Methods: This retrospective study involved the examination of 26 NTOS patients who underwent piezo surgery and another group of 30 patients who underwent FRR using the conventional technique. In the patient group that underwent piezo surgery, the rib was first resected into two pieces using a piezoelectric device and subsequently removed. In the patient group that underwent conventional surgery, the first rib was removed as one piece using a rib cutter and rongeurs. Results: The piezo surgery group had significantly shorter operative time (96.85 ± 14.66 vs. 143.33 ± 25.64 min, P < 0.001) and FRR duration (8.73 ± 2.11 vs. 22.23 ± 6.27 min, P < 0.001) than the conventional group. The posterior stump length of the residual rib was shorter in the piezo surgery group than in the conventional group (0.54 ± 0.19 vs. 0.65 ± 0.15 cm, P < 0.05). There were no significant differences in postoperative complications and scores of the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire, the Cervical Brachial Symptom Questionnaire (CBSQ), and the visual analog scale (VAS). Even the TOS index (NTOS Index= [DASH + (0.83 × CBSQ) + (10 × VAS)]/3) and patient self-assessments of both the groups showed no significant differences. Univariate analyses indicated that the type of treatment affected operative time. Conclusion: Our results suggest that piezo surgery is safe, effective, and simple for segmental FRR in NTOS patients. Piezo surgery provides a more thorough FRR without damaging adjacent soft tissues in a relatively short duration and achieves similar functional recovery as conventional techniques. Therefore, piezo surgery can be a promising alternative for FRR during the surgical treatment of NTOS.